Banking reform, risk-taking, and earnings quality – Evidence from transition countries - Yiwei Fang; Iftekhar Hasan; Lingxiang Li (Bank of Finland, Institute for Economies in Transition (BOFIT), 2014)
​The dynamic banking reforms of Central and Eastern Europe (CEE) following the collapse of the Soviet Union provide an ideal research setting for examining the causal effect of institutional development on financial reporting. Using five earnings quality measures, we consistently find that banking reform improves accounting quality and reduces earnings management incentives in the 16 transition countries considered. The results strongly hold in our within-country and difference-in-difference models, as well as in non-parametric analyses. We also find supporting evidence for the notion that excessive risk-taking of banks impairs earnings quality. As a result, banking reform improves earnings quality partially through its ability to curb risk-taking behavior. Publication
URN:NBN:fi:bof-201411243343
Keywords: G18; M41; M48; G38; E50; G15; 330; earnings management; earnings quality; institutional development; bank risk-taking